MENINGKATKAN KINERJA GURU MELALUI KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN IKLIM ORGANISASI DI MADRASAH - Januar Barkah (Universitas Indraprasta PGRI, 2014)
The purpose of the study to determine the effect of the principal managerial capabilities and organizational climate on the performance of school teachers. The research used a descriptive quantitative data collection techniques with questionnaires. There is a positive effect of managerial ability principals on teacher performance Madrasah Aliyah Negeri 13 Jakarta. There is a positive effect of organizational climate on the performance of Teachers of Madrasah Aliyah Negeri 13 Jakarta. There is a positive effect of managerial ability of principals and organizational climate on teacher performance Madrasah Aliyah Negeri 13 Jakarta. While the results of the value of R2 (R Square) is 0.417. This shows that for 41.7% headmaster managerial capabilities and organizational climate jointly positive effect on teacher performance while the remaining 57.3% influenced by other factors that are not observed by the authors.Keywords: Managerial Ability Principals, Organizational Climate and Teacher Performance